Implementasi PPDM Tahun Pertama bagi Masyarakat Pesisir Danau Limboto melalui Penguatan Sumber Daya Manusia dan Iptek Manajemen Pemanfaatan Eceng Gondok sebagai Produk Unggulan - Tineke Wolok; Ismet Sulila; Weny Almoravid Dungga (Universitas Mathla'ul Anwar Banten, 2019)
THE IMPLEMENTATION OF PPDM FIRST YEAR FOR PEOPLE OF COAST OF LAKE LIMBOTO THROUGH ENFORCEMENT OF HUMAN RESOURCE AND SCIENCE AND TECHNOLOGY (IPTEK) OF MANAGEMENT OF WATER HYACINTH USE AS EXCELLENT PRODUCT. Iluta Village is situated in coastal of Limboto Lake and frequently encounters flood problem in the rainy season and also serious problem namely siltation of Limboto Lake as caused by the massive growth of water hyacinth. There were three main problems handled by this program at the first year, namely: 1) effort of reducing siltation of Limboto Lake sustainably through removal and use of the water hyacinth as craft material, 2) empowerment of community economic through capacity building of business management of varied water hyacinth woven crafts, and 3) capacity building of human resource of local community as target group. The applied method encompassed: 1) determining problems priority to be solved and divided them into three-year activity, 2) doing reconstruction and improvement based on the problems gradually for every year, 3) improvement was performed based on local community character approach. The findings showed: 1) use of water hyacinth as handicrafts product could help reducing Lake Siltation, 2) management ability in business management started to grow, and 3) improvement of human resource ability for the coastal community as the target group.